The crystal structure of fac-tricarbonyl(2-pyridin-2-yl-quinoline-κ2 N,N′)-(pyrazole-κN)rhenium(I)nitrate, C20H14N4O3ReNO3 - Sithole Sibusiso A.; Malan Federick P.; Katerere David R.; Manicum Amanda-Lee E. (Zeitschrift für Kristallographie - New Crystal Structures)
C20H14N4O3 ${C}_{20}{H}_{14}{N}_{4}{O}_{3}$ ReNO3 ${NO}_{3}$ , monoclinic, P21 ${2}_{1}$ /c (no. 14), a = 12.9572 (2), b = 9.1568 (2), c = 17.3658 (3) Å, β = 97.267(2)° $97.267(2){}^{°}$ , V = 2043.84 (7) Å3 ${\mathrm{\mathring{\text{A}}}}^{3}$ , Z = 4, Rgt ${R}_{gt}$ (F) = 0.0231, wRref $wR_{ref}$ (F2 ${F}^{2}$ ) = 0.0514, T = 154 K